EFFORTS TO FORCE THE IMPLEMENTATION OF THE COURT RULING THE COUNTRY IN PROVIDING LEGAL PROTECTION TO THE COMMUNITY - ,SH, Lubna (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
This research aims to analyze efforts towards implementation of the Court decision forced The Countryâs Efforts in providing legal protection to the community. The legal issues that arise in this research include: How the implementation effort forced The Court ruling against the State in providing legal protection to the public and factors what are the obstacles in the implementation of the ruling of the Administrative Court of the State. This research is the normative legal research based on the consideration that this study departs from a Legislation Regulatory analysis explains the legal aspects related tho the forced attempts against the Court ruling The country. The approach used is a statutory approach, approach to the concept, approach comparison. Legal materials collection techniques with the study of librarianship. After it is done processing the law by holding systematization then do reasoning logically and systematically with descriptive qualitative analysis and draw conclusions by deductive way. Based on the results of the study it can be concluded, that a comparison of forced efforts against the Court ruling between Indonesia and Thailand has a lot in common countries, in Indonesia have less strict attitude in enforcing the law and provide protection to the community with regard to the implementation of the ruling of the Administrative Court of the State. In addition, the implementing rules, there is not a more detailed regarding the implementation of the forced attempts againts the Court ruling The country. The State Administrative Court need movement in creating the rules and regulations implementing the unequivocal.Keywords: Effort force, Court rulings, Legal protection.